Congressional statecraft and the Rise of US-India Strategic Convergence: From civil Nuclear cooperation to Critical Technologies - Mehar Sandhu (Journal of Daoist Studies, 2026)
Abstract: The evolution of United States–India relations over the past two decades represents one of the most consequential strategic realignments in contemporary international politics. While much of the existing scholarship attributes this transformation to changing geopolitical realities, particularly the rise of China and the growing importance of the Indo-Pacific, less attention has been paid to the role of domestic institutions in shaping this trajectory. This article examines the contribution of the United States Congress to the development of the bilateral partnership, arguing that congressional action has been central to the institutionalization of strategic cooperation between the two countries. The study traces the progression of the relationship from the negotiation and approval of the U.S.–India Civil Nuclear Agreement to current collaboration in critical and emerging technologies. Drawing upon a historical-institutionalist framework, the article demonstrates how congressional support for nuclear cooperation generated a foundation of political trust and policy continuity that subsequently facilitated deeper engagement in areas such as defense innovation, semiconductor supply chains, artificial intelligence, quantum technologies, and advanced manufacturing. Rather than functioning solely as an oversight body, Congress emerged as an active participant in reshaping the strategic logic of U.S. engagement with India. The article concludes that congressional statecraft has played a significant role in transforming bilateral ties into a multidimensional partnership that increasingly occupies a central place in the strategic architecture of the Indo-Pacific.